2005
DOI: 10.1177/0743558405275086
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Perceptions of Changes in Mother-Child and Father-Child Relationships During Adolescence

Abstract: Little research has examined parents'experiences of their children's transition to adolescence. The authors studied a sample of 170 mothers' and 159 fathers' open-ended descriptions of their experiences and investigated the role of prior relationship quality in predicting the nature of parents' experiences. Changes in the personal qualities of children, general closeness in the parent-adolescent relationship, and communication emerged as features of relationship change most salient to parents. Changes in paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
4
33
0
1
Order By: Relevance
“…It is possible the significant correlations support the assertion of Gecas and Schwalbe (1986) that parental involvement is a means to convey to children indicators of their own self-worth. Moreover, the correlations appear to support the expected value of parents' relationship to adolescent self-esteem despite the ostensible ambiguity in parenting roles during adolescence (Henricson and Roker 2000) and the increasing autonomy of adolescents (Shearer et al 2005). This finding is especially salient given the involvement of both mothers and fathers each independently relate to adolescent self-esteem.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It is possible the significant correlations support the assertion of Gecas and Schwalbe (1986) that parental involvement is a means to convey to children indicators of their own self-worth. Moreover, the correlations appear to support the expected value of parents' relationship to adolescent self-esteem despite the ostensible ambiguity in parenting roles during adolescence (Henricson and Roker 2000) and the increasing autonomy of adolescents (Shearer et al 2005). This finding is especially salient given the involvement of both mothers and fathers each independently relate to adolescent self-esteem.…”
Section: Discussionmentioning
confidence: 64%
“…As a child moves through adolescence, one change in parenting includes less parental supervision because adolescents begin to possess more responsibility for regulating themselves (Shearer et al 2005). This increase in adolescent autonomy is often accompanied by other changes in the parent-adolescent relationship, such as decreased feelings of closeness and attachment to parents (Steinberg and Silk 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Regardless of gender differences between fathers and mothers, how does the parent-child interaction between fathers and mothers differ from each other? In terms of mothers, the interaction relationship between mothers and children presents more connection and involvement and children also think that the relationship between them and their mothers is much closer (Laursen, Wilder, Noack, & Williams, 2000;Shearer, Crouter & McHale, 2005). Shearer et al (2005) also found that children expressed that mothers understood them better than fathers.…”
Section: The Differences In Parent-child Interaction Relationship Typesmentioning
confidence: 89%
“…In terms of mothers, the interaction relationship between mothers and children presents more connection and involvement and children also think that the relationship between them and their mothers is much closer (Laursen, Wilder, Noack, & Williams, 2000;Shearer, Crouter & McHale, 2005). Shearer et al (2005) also found that children expressed that mothers understood them better than fathers. Other researchers also found that mothers have more experience with interacting with or taking care of their children, whereas the interactions between fathers and children were more likely to relate to instrumental goals, such as sports achievement or cultivation of future plans (Lawson & Brossart, 2004;Russell, Hart, Robinson, & Olsen, 2003;Shearer et al, 2005).…”
Section: The Differences In Parent-child Interaction Relationship Typesmentioning
confidence: 89%
“…The relationship between parent and child is not necessarily linear over time however (Tsai et al, 2013). Despite the underlying understanding that adolescence is a rather turbulent time, research has shown that various changes and disruptions in family dynamics across the adolescent years are typically short-lived, and that changes in family relationships during adolescence are generally moderate in size (Shearer, Crouter, & McHale, 2005). Within-family socialization has been described as a sequential process in which the parent-child relationship changes dramatically as children grow older, with each new phase emerging from of the parent-child relationship established earlier (Grusec & Hastings, 2015).…”
mentioning
confidence: 99%